DEEP LEARNING FOR SYMBOL RECOGNITION IN MODERN ART - Gopinath K; Patil, Shashikant; Aulakh, Damanjeet; Parmar, Dhara; Singh, Priyadarshani; Patil, Pradnya Yuvraj (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Modern art has symbolism, which goes beyond the literal, bringing its meaning in the form of abstraction, geometry, and color. This paper outlines a hybrid deep-learning model that is a combination between the fields of artistic semiotics and computational perception to conduct automated recognition of symbols in contemporary and modern artworks. The given architecture is a combination of Convolutional Neural Networks (CNNs) to analyze local texture and form with Transformer encoders to process global contexts and provide an opportunity to understand symbolic patterns in a nuanced manner. An annotated collection of ontology-guided taxonomies based on Icon class and the Art and Architecture thesaurus (AAT), was conducted on a curated collection of multiple art movements Cubism, Surrealism, Abstract Expressionism, and Neo-Symbolism. The experimental findings prove that the hybrid model (mAP = 0.86, F1 = 0.83) works well than traditional architectures, which proves the synergy between the visual perception and semantic attention mechanisms. Interpretive transparency is also supported by visualization with Grad-CAM and attention heatmap, as it makes computational focus consistent with the symbolic cues added by humans. The framework also enables AI-assisted curation, digital archiving and art education on top of technical precision, so the framework introduces the notion of computational empathy the ability of the machine to recognize cultural meaning in the form of learned representations. The study highlights the opportunities of deep learning to expand the scope of art interpretation beyond data analytics, to semantic and cultural interpretation, as a prerequisite of intelligent and inclusive art-technology collaboration.